2021
DOI: 10.21203/rs.3.rs-405544/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Benefits of Betanin in Rotenone-Induced Parkinson Mice

Abstract: The present study aimed to investigate betanin’s neuroprotective effect in mice with rotenone-induced Parkinson-like motor dysfunction and neurodegeneration. Forty male ICR mice were divided into 4 groups: Sham-veh, Rot-veh, Rot-Bet100 and Rot-Bet200. Rotenone (Rot) at 2.5 mg/kg/48 h was subcutaneous injected, and betanin (Bet) at 100 and 200 mg/kg/48 h were given alternately with the Rot injections in Rot-Bet groups for 6 weeks. Motor dysfunctions were evaluated weekly using hanging wire and rotarod tests. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Hydroxyl radicals as a cascade product originating from O2can exacerbate damage via lipid peroxidation, as indicated by an increased MDA level during IR [33]. Similar to other studies, we showed that IR led to increased MDA and that betanin helped reduce MDA [9,17,34]. Betanin inhibited this toxic metabolite of lipid peroxidation, depending on its cyclic amine and hydroxyl groups, which act as good hydrogen and electron donors [35].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Hydroxyl radicals as a cascade product originating from O2can exacerbate damage via lipid peroxidation, as indicated by an increased MDA level during IR [33]. Similar to other studies, we showed that IR led to increased MDA and that betanin helped reduce MDA [9,17,34]. Betanin inhibited this toxic metabolite of lipid peroxidation, depending on its cyclic amine and hydroxyl groups, which act as good hydrogen and electron donors [35].…”
Section: Discussionsupporting
confidence: 87%
“…Betanin's neuroprotective efficacy includes its potent antioxidative properties, such as its inhibitory effect on lipid peroxidation by attenuation of malondialdehyde (MDA) levels. Betanin also helped reduced glutathione (GSH), catalase (CAT) and superoxide dismutase (SOD) activities [9,10]. Dugger and Dickson [11] found evidence of many pathomechanism-joining degenerative diseases, such as oxidative stress and inflammation.…”
Section: Introductionmentioning
confidence: 99%